Belowground biomass C outweighs soil organic C of perennial energy crops: Insights from a long‐term multispecies trial. Issue 3 (9th January 2021) - Martani, Enrico; Ferrarini, Andrea; Serra, Paolo; Pilla, Marcello; Marcone, Andrea; Amaducci, Stefano
Abstract: The cultivation of perennial energy crops (PECs) couples the production of ligno‐cellulosic biomass to the provision of multiple ecosystem services, such as the reduction of greenhouse gas emissions and the mitigation of climate change through carbon (C) sequestration in soil. Though C sequestration in soil by PECs has been widely studied, the contribution of their belowground biomass (BGB) to soil C sequestration and their influence on soil nitrogen (N) storage potential has received very little attention. In this study, C and N stocks in soil and BGB fractions (plant belowground organs and fine roots) were measured for six PECs ( Populus spp. 'Poplar', Robinia pseudoacacia 'Black locust', Salix spp. 'Willow', Arundo donax 'Giant reed', Miscanthus × giganteus 'Miscanthus' and Panicum virgatum 'Switchgrass') grown on marginal soil, 11 years after establishment. All PECs had a higher soil organic carbon (SOC) stock and soil total nitrogen (STN) stock than arable land in the top (0–10 cm) soil layer. In this same top layer, woody crops had the highest SOC stock. The increase in SOC under PECs led to increased soil porosity in the top‐soil layer. On average, 43% of the belowground C stock of PECs was allocated in the plant belowground organs (PBO; i.e. in the rhizomes of herbaceous PECs and the stump for woody PECs). Giant reed had the highest C stock in PBO, whereas switchgrass the lowest (22.7 vs. 5.9 Mg C ha −1 ). On the contrary, switchgrass had the highest C stock in fine roots. Giant reed had the highest belowground C stock (sum of soil and BGB contribution) and black locust the highest belowground N stock. After 11 years of PEC cultivation, 68% of the belowground C stock was allocated in the BGB, and 32% was as SOC. Abstract : Eleven years of perennial energy crops (PECs) cultivation on marginal lands lead to sequester in the first 30 cm of soil 0.48 Mg SOC ha year −1 under herbaceous PECs and of 0.50 Mg C ha year −1 under woody PECs. In the potential re‐convertible layer (0–30 cm), PECs accumulated more C in the belowground biomass (BGB) than in soil while in subsoil (30–100 cm) more C was stored in soil than in the BGB. In subsoil herbaceous PECs stored more C than woody PECs.